Effects of Selenium Nanoparticles Combined With Radiotherapy on Lung Cancer Cells - Tian, Jingxia; Wei, Xiaoying; Zhang, Weihua; Xu, Aiguo (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: To investigate the effects of selenium nanoparticles (nano-Se) combined with radiotherapy on the proliferation, migration, invasion, and apoptosis of non-small cell lung cancer (NSCLC) A549 and NCI-H23 cells. Methods: Nano-Se was synthesized and characterized by transmission electron microscope (TEM), X-ray diffractometer, and Ultraviolet-visible (UV)-Vis Spectroscopy, separately. The uptake of nano-Se by lung cancer cells was detected by flow cytometry. Cell counting kit-8 (CCK-8) method was used to detect the antiproliferative activity of nano-Se combined with radiotherapy. Wound healing tests and transwell assay were used to detect the migration and invasion ability of the cells. Annexin-V fluoresceine isothiocyanate (FITC)/ Propidium iodide (PI) staining by flow cytometry was used to detect apoptosis. The expression of Cyclin D1 (CCND1), c-Myc, matrix metalloproteinase 2 (MMP2), MMP9, cleaved Caspase-3, and cleaved Caspase-9 were detected by Western blot. Results: The average diameter of nano-Se was 24.39 nm and the wavelength of nano-Se increased with the increase of radiation dose under UV-Vis Spectroscopy. The uptake of nano-Se in lung cancer cells was increased with the increase of nano-Se concentration. The nano-Se combined with radiotherapy decreased the proliferation activity of NSCLC cell lines A549 and NCI-H23 in a dose-dependent manner (all P<0.05). Compared with the Control group, nano-Se combined with radiotherapy could significantly inhibit the migration and invasion of lung cancer cells (all P<0.05), and the effects of the combination of nano-Se and radiotherapy was better than that of a single application (all P<0.05). Furthermore, nano-Se combined with radiotherapy could induce apoptosis of lung cancer cells (P<0.05) and nano-Se combined with radiotherapy could significantly inhibit the expression of proliferation-related proteins CCND1, c-Myc, invasion and migration-related proteins MMP2 and MMP9, but conversely promoted the expression of apoptosis-related proteins cleaved caspase-3 and cleaved caspase-9. Conclusion: This study found that nano-Se combined with radiotherapy plays an anti-cancer role in lung cancer cells by inhibiting cell proliferation, migration, and invasion, as well as inducing apoptosis, suggesting that nano-Se may be used as a radiosensitizer in the clinical treatment of lung cancer, but further research is still needed.